Effective Combination Therapy with Human Amniotic Membrane Mesenchymal Stem Cells and Low-Level Laser Therapy in Wound Healing in Animal Models: Human Amniotic Membrane Mesenchymal Stem Cells and Low-Level Laser Therapy in Wound Healing - Abbasnezhad, Fatemeh; Zare, Sona; Razzaghi, Mohammadreza; Karjou, Reza; Karjou, Zahra; Zadehmodarres, Shahrzad (Journal of Lasers in Medical Sciences, 2022)
Introduction: Many studies have recognized the importance of new methods in wound healing. This study aims to investigate the healing effects of allograft extra embryonic mesenchymal stem cells (MSCs) with and without low-level diode laser irradiation when grafted into full-thickness skin defects in diabetic animal models. Methods: In this experimental study, in order to make the rats diabetic, we used an intra-peritoneal injection of streptozotocin. Human amniotic membrane derived mesenchymal stem cells (hAMSCs) were irradiated with a low-level diode laser. Two full-thickness excisions were made on the backs of the rats. Next, the rats were divided into the following groups: group 1: low-level laser (LLL) irradiated hAMSCs, and group 2: hAMSCs alone transplanted into skin wounds. Histopathologic, ultrasound, and elasticity evaluations were performed 7, 14 and 21 days after grafting. Results: In the evaluated rats, the epithelial formation was on day 7 and increased until day 14. On days 7, 14 and 21, the percentage of epithelial formation in the irradiated cell group was significantly higher than that in the cell group, so that, on day 21, the epithelium in this group completely covered the wound surface while in the control group, the wound surface was still not completely covered. In terms of angiogenesis, on day 7, the irradiated cells were significantly lower than the cells. Also, the formation of collagen in the cellular hydrogel group could confirm the effectiveness of amniotic MSCs in collagen production and thus accelerate the wound healing process. In comparison with hAMSCs alone, irradiated hAMSCs increased the thickness and elasticity of the skin. Conclusion: Low-power lasers along with MSCs can be effective in improving chronic wound conditions in the animal model.